Role of inflammatory markers in predicting mortality and outcome of acute encephalitis syndrome in children of Eastern Uttar Pradesh India - Singh, Kamaldeep; Sharma, Bhoopendra; Singh, Vijay Kumar; Singh, Priyanka (International Journal of Contemporary Pediatrics, 2024)
Background: The present study was performed to study the role of inflammatory markers viz. C-reactive protein, procalcitonin, serum ferritin and serum lactate dehydrogenase in predicting the mortality and outcome in patients with acute encephalitis syndrome admitted to pediatrics ICU, BRD medical college, Gorakhpur. Methods: 140 patients/children of the age group ranging from 1 year to 16 years admitted in the acute encephalitis syndrome unit of BRDMC during 1 August 2021 to 31 July 2022 were analyzed with the prospective observational study. Results: Vaccination status (p<0.001) and socioeconomic status (p=0.020) were associated with mortality outcome in AES patients. Serum procalcitonin levels with cut off value >0.10 mg/dl and serum LDH levels with cut off value of 480u/L have shown a positive association with the mortality in AES patients. (p=0.041 and p=0.038, and strength of association is 0.67 and 0.65, respectively. C-reactive protein with a cut-off value 10 mg/dl and serum ferritin with a cut-off value 140 ng/ml have shown no association with mortality with p values of 0.143 and 0.267, respectively. The Area under the ROC curve is maximum for serum procalcitonin (0.937) with a cut-off value 0.10 ng/dl with 100% sensitivity and 75.8% specificity (confidence interval 95%: 0.894-0.980). The negative predictive value is 100% and PPV is 13.7%. Similarly, the area under the ROC curve for CRP with a cut-off 10mg/dl is 0.900 (confidence interval 95%: 0.841-0.959) with 100% sensitivity of and 64.8%. specificity. Consequently, the negative predictive value is 100 % and the positive predictive value of 11.1%. Conclusions: For predicting the mortality in AES patients 2 prognostic markers viz. C reactive protein and procalcitonin can prove to be promising prognostic screening tests, and therefore, both the tests are advised consecutively.